2017
DOI: 10.1589/jpts.29.2004
|View full text |Cite
|
Sign up to set email alerts
|

Changes in fatigue and physical function with age for patients with gastrointestinal cancer in the perioperative period: a comparison between older and young patients

Abstract: [Purpose] The purpose of this study was to examine changes in fatigue and physical function with age for groups of patients with gastrointestinal cancer in the perioperative period. [Subjects and Methods] The study involved 52 patients with gastrointestinal cancer (28 males and 24 females, aged 62.4 ± 12.0 years). The subjects were divided into two groups: those 65 or over (the so-called elderly group,) and those 64 or under (the so-called young group). The six minute walk distance (6MWD), Cancer Fatigue Scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
4
1
0
Order By: Relevance
“…Although there was no statistically significant difference in the study, mean fatigue scores of the individuals graduated from primary school. Our findings are consistent with the literature (16)(17).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Although there was no statistically significant difference in the study, mean fatigue scores of the individuals graduated from primary school. Our findings are consistent with the literature (16)(17).…”
Section: Discussionsupporting
confidence: 94%
“…In our study, the difference between mean score of hope level and gender, age, marital status, educational status and employment was not statistically significant. In literature, although women are reported to be more disadvantaged than males in situations, such as mood disorders, depression and self-annihilation (19), there are also studies indicating no gender difference in terms of hope (16)(17). Our findings are consistent with the literature (20).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We observed exercise capacity and physical functioning reduced post-surgery ( Table 2 ), with significant differences between the new Japanese elderly standard age groups. This is consistent with previous studies linking this to an age effect 3 , 4 , 11 , 12 ) . This suggests that this new Japanese elderly standard captures the age-related reduction in exercise capacity in patients with gastrointestinal cancer.…”
Section: Discussionsupporting
confidence: 93%
“…Previous work around the world has shown that aging of patients with gastrointestinal cancer increases perioperative risk factors, such as onset of postoperative complications 1 , 2 ) , reduces postoperative health-related quality of life (HRQOL) 3 ) and also reduced physical function after surgery 4 ) . The International Society of Geriatric Oncology and National Comprehensive Cancer Network recommend the incorporation of geriatric assessment in treatment planning 5 , 6 , 7 ) .…”
Section: Introductionmentioning
confidence: 99%